The clinical characteristics of COVID-19 omicron variant infection in pregnant women and their neonates - Liu, Li-Li; Lin, Lv-Hua; Lin, Fen; Yang, Yi-Kang; Lin, Chun-Fan; Zhang, Lin; Huang, Yu-Chan; Liao, Yu-Wei; Zeng, Yan-Qing; Zeng, Guang-Kuan; Cao, Yan-Bin; Zhu, Rui-Zhen; et al. (Frontiers in Medicine, 2023)
Objective The objective of this study was to analyze the clinical characteristics of pregnant women infected with the COVID-19 omicron variant and their neonates during the outbreak in Guangdong province, China. Methods The clinical data of pregnant women infected with the COVID-19 omicron variant and their neonates were retrospectively collected from two hospitals in Guangdong province. Information recorded included age of mother, date of birth, sex, weight at birth, mode of delivery, gestational age, feeding mode, Apgar score, signs, medical records, underlying comorbidities and laboratory results. The presence of SARS-CoV-2 viral RNA was tested using an real-time PCR assay. Results Seventy-nine pregnant women infected with COVID-19 omicron variant and their 68 neonates were included in this study. The vast majority (86.1%) of pregnant women was in their third trimester of pregnancy, and only 11 cases (15%) were in the first or second trimester. Of 79 pregnant women, 39 cases were asymptomatic at the time of infection, and 40 mothers presented with mild manifestations of COVID-19. The most common symptoms were fever (92.5%, 37/40) and cough (57.5%, 21/40). All of pregnant women did not receive chest computed tomography (CT) scan or X-ray. No pregnant woman developed severe pneumonia. A total of 68 neonates (3 set of twins) from 65 mothers with COVID-19 were reviewed. Among women who delivered, 34 cases underwent cesarean section, 31 cases underwent vaginal delivery. According to the timing of birth, there were 10 (14.7%) preterm neonates. Two babies were born dead (intrauterine fetal death after 22 weeks of gestation). Of the live babies born (66 cases) from mothers with COVID-19, 9 newborns were lower weight, and one preterm case was born with respiratory distress and intubated, he recovered and developed normally. SARS-CoV-2 nucleic acid testing was conducted on 41 neonates daily after birth, with only one neonate testing positive for SARS-CoV-2 infection on the third day after birth. The infected neonate exhibited typical fever and acute respiratory tract syndrome but ultimately had a good prognosis, recovering after 5 days of treatment. Conclusion Although preliminary data suggests the risk of severe maternal and fetal complications from Omicron variant infection during pregnancy is lower than previous variants and Delta variant. Our study, which was conducted on a limited population sample, indicates that there is a possibility of severe complications, such as stillbirth, occurring in some fetal cases. These findings emphasize the need for continued attention from obstetricians.